Quantifying the factors limiting rate performance in battery electrodes - Ruiyuan Tian (Nature Portfolio, 2019)
The authors employ a semi-empirical method to fit published battery capacity-rate data to extract the characteristic time associated with charge/discharge. These characteristic times are consistent with a physical model that can be used to link rate performance to the physical properties of electrodes.